2016
DOI: 10.12693/aphyspola.129.244
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Human Lenses by Raman Microspectroscopy

Abstract: A cataract is an opacity (clouding) of the normally clear lens which develops as a result of aging, metabolic disorders, trauma or heredity. The number of patients with cataract is increasing exponentially. This disease requires surgical intervention, to remove the cloudy lens and to introduce the eye lens polymer. In this work we will present analyses of degraded parts of human lens. Experimental materials were obtained from the lens removed during surgical intervention. These biological samples were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Paluszkiewicz et al reported the Raman spectrum from two human lenses after cataract surgery. They found an excess of tryptophan, tyrosine, phenylalanine, Beta-sheet, the cause being still under discussion [11]. In comparing healthy and cataractous human lenses with Raman spectroscopy, they found differences in the concentration of Tyr and Trp residues [12].…”
Section: Introductionmentioning
confidence: 98%
“…Paluszkiewicz et al reported the Raman spectrum from two human lenses after cataract surgery. They found an excess of tryptophan, tyrosine, phenylalanine, Beta-sheet, the cause being still under discussion [11]. In comparing healthy and cataractous human lenses with Raman spectroscopy, they found differences in the concentration of Tyr and Trp residues [12].…”
Section: Introductionmentioning
confidence: 98%
“…In a clinical setting, a preferred option would be a non-invasive and non-destructive technique [17]. We propose to use Raman spectroscopy as a non-invasive and non-destructive sampling technique [8,[17][18][19][20][21]. In this study, IL-10, IL-21 and ACE samples were tested.…”
Section: Introductionmentioning
confidence: 99%
“…They found an excess of tryptophan, tyrosine, phenylalanine, Beta-sheet, the cause being still under discussion. 68 In comparing healthy and cataractous human lenses with Raman spectroscopy, they found differences in the concentration of Tyr and Trp residues. 69 Biomarkers for eye diseases like TNF alpha (Tumor necrosis factor alpha), Cytochrome C, Lactate acid, Lysozyme and Vascular Endothelial Growth Factor (VEGF) [70][71][72][73] have been shown to be Raman active and their characteristic Raman spectra have been obtained by different research groups.…”
Section: Raman Spectroscopy Applications In Ophthalmologymentioning
confidence: 99%